A Cosmic Liturgy: Qumran's 364-Day Calendar - Osborne, Alfred (Brepols, 2019)
This work shows how the importance of Sunday, Wednesday, and Friday in the 364-day Qumran calendar is based on the Priestly creation narrative in Genesis and the myth of a cosmic covenant established between God and the angels on the first day. The myth of the apostasy of the angels guiding the seven planets was used to explain the discrepancy between the 364-day calendar and observation. The Epistle of Jude makes it possible to situate this work in relation to both <span class=